The impact of supported accommodation on health and criminal justice outcomes of people released from prison: a systematic literature review - Daisy Gibbs; Emily Stockings; Sarah Larney; Daniel J. Bromberg; Anthony Shakeshaft; Sara Farnbach (BMC, 2023)
Abstract Background Supported accommodation intends to address challenges arising following release from prison; however, impact of services, and of specific service components, is unclear. We describe key characteristics of supported accommodation, including program components and outcomes/impact; and distil best-evidence components. Methods We conducted a systematic review, searching relevant databases in November 2022. Data were synthesised via effect direction plots according to the Synthesis Without Meta-analysis guidelines. We assessed study quality using the McGill Mixed Methods Appraisal Tool, and certainty in evidence using the GRADE framework. Results Twenty-eight studies were included; predominantly cross-sectional. Program components which address life skills, vocational training, AOD use, and mental health appear to positively impact criminal justice outcomes. Criminal justice outcomes were the most commonly reported, and while we identified a reduction in parole revocations and reincarceration, outcomes were otherwise mixed. Variable design, often lacking rigour, and inconsistent outcome reporting limited assessment of these outcomes, and subsequently certainty in findings was low. Conclusion Post-release supported accommodation may reduce parole revocations and reincarceration. Despite limitations in the literature, the findings presented herein represent current best evidence. Future studies should clearly define program components and measure their impact; use analyses which reflect the high risk of adverse outcomes, such as time-to-event analyses; and consider outcomes which reflect the range of challenges faced by people leaving prison. Registration: PROSPERO registration CRD42020189821.